Does muscle imbalance affect fatigue after soccer specific intermittent protocol? - de Abreu Camarda, Sergio Ricardo [UNESP]; Denadai, Benedito Sergio [UNESP] (Elsevier B.V., 2012)
Objectives: This study investigated the muscular strength imbalance dependence of the effect of fatigue induced by an exhaustive laboratory-based soccer-specific exercise on different hamstrings:quadriceps (H:Q) ratios of soccer players.Design: Repeated measures.Methods: Twenty-one male professional soccer players (23.2 +/- 3.5 years) performed a pre-test to assess the concentric (con) and eccentric (ecc) strength of the knee extensors (KE) and flexors (KF) at 60 degrees s(-1) and 180 degrees s(-1). Then performed an exhaustive laboratory-based soccer-specific exercise and a post-test similar to the pre-test. The players were allocated into one of two groups in accordance to their conventional H-con:Q(con) (balanced group, BG=H-con:Q(con)>0.60; unbalanced group, UNBG=H-con:Q(con)<0.60).Results: The KEcon (BG=4%, p<0.05: UNBG=6%, p<0.01) and KFcon (BG=7%, p<0.01; UNBG=8%, p<0.01) at 60 degrees s(-1) were significantly reduced after exercise for both groups. However, KFecc at 180 degrees s(-1) was significantly reduced only in BG (16%, p<0.01). The H-con:Q(con) and H-ecc:Q(con) were significantly reduced after exercise in BG (0.65 +/- 0.03 vs. 0.62 +/- 0.04, p<0.05; 1.38 +/- 0.2 vs. 1.20 +/- 0.2, p<0.01; respectively), but not in UNBG (0.55 +/- 0.04 vs. 0.54 +/- 0.07; 1.19 +/- 0.1 vs. 1.13 +/- 0.2, respectively).Conclusions: The effect of fatigue induced by an exhaustive laboratory-based soccer-specific exercise on H-con:Q(con) and H-ecc:Q(con) in the dominant leg of professional soccer players is dependent on muscular strength balance. Thus, experimental designs and prevention programmes should consider that muscular strength balance might also module the game-induced fatigue of professional soccer players. (c) 2011 Sports Medicine Australia. Published by Elsevier Ltd. All rights reserved.
Keywords: Isokinetic; Hamstring; Injury